Social Commerce Among Micro and Small Medium Enterprises Before and During the COVID19: A Systematic Literature Review - Omar M.A.; Sulaiman R.B. (Natural Sciences Publishing, 2024)
Social commerce (SC) is a relatively new tool that businesses are using to conduct business using social media (SM). The findings of prior literature are inconclusive. This paper reviews the literature to identify the current status and to identify the determinant of SC. A systematic literature review was conducted. A total of 41 articles were reviewed. A comparison between before and during COVID19 was conducted. The findings showed the number of studies has not increased during COVID-19. The technology acceptance model (TAM) and Technology-Organization-Environment (TOE) are used widely in the literature. The most important factors identified in this study are divided into before COVID19 and during COVID19. Perceived usefulness and perceived ease of use were important in both periods. New variables that were considered important during COVID19 is the organizational readiness, trust, security, and E-word of mouth (EWOM). More research is needed to understand the factors that contribute to SC adoption in different nations. Variables such as trust, environmental uncertainty, and perceived value can be included in future work. Developing a digital ecosystem for SC is a direction for future work. Understanding the important factors can contribute to the advancement of SC. 2023 NSP Natural Sciences Publishing Cor.